Environmental law, the economy, and sustainable development the United States, the European Union, and the international community - Revesz, Richard L. 1958-; Sands, Philippe 1960-; Stewart, Richard B. 1940- (Cambridge University Press, 2000)
This book provides a comparative analysis of environmental regulation in multi-jurisdictional legal and political systems, focusing on the United States, the European Union, and the international community. Each of these systems must deal with environmental interdependencies that cross local borders. Some transjurisdictional environmental problems are global, including stratospheric ozone depletion, climate change and the loss of biodiversity. Other environmental problems, however, are localized in their effect on health and the environment: for example, municipal waste disposal, many forms of pollution and resource development, and drinking water quality. These varying jurisdictional and environmental circumstances pose the central question of how responsibility for addressing different environmental problems should be allocated among the different levels of decision making and implementation in a multi-jurisdictional system
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Nachhaltigkeit; Recht; Environmental law / United States; Environmental law / Europe; Sustainable development / Law and legislation; Environmental economics; Umweltökonomie; Internationales Umweltrecht; Europa; USA